Regulators involved in trophoblast syncytialization in the placenta of intrauterine growth restriction - Zhou, Hanjing; Zhao, Chenqiong; Wang, Peixin; Yang, Weijie; Zhu, Haiyan; Zhang, Songying (Frontiers in Endocrinology, 2023)
Placental dysfunction refers to the insufficiency of placental perfusion and chronic hypoxia during early pregnancy, which impairs placental function and causes inadequate supply of oxygen and nutrients to the fetus, affecting fetal development and health. Fetal intrauterine growth restriction, one of the most common outcomes of pregnancy-induced hypertensions, can be caused by placental dysfunction, resulting from deficient trophoblast syncytialization, inadequate trophoblast invasion and impaired vascular remodeling. During placental development, cytotrophoblasts fuse to form a multinucleated syncytia barrier, which supplies oxygen and nutrients to meet the metabolic demands for fetal growth. A reduction in the cell fusion index and the number of nuclei in the syncytiotrophoblast are found in the placentas of pregnancies complicated by IUGR, suggesting that the occurrence of IUGR may be related to inadequate trophoblast syncytialization. During the multiple processes of trophoblasts syncytialization, specific proteins and several signaling pathways are involved in coordinating these events and regulating placental function. In addition, epigenetic modifications, cell metabolism, senescence, and autophagy are also involved. Study findings have indicated several abnormally expressed syncytialization-related proteins and signaling pathways in the placentas of pregnancies complicated by IUGR, suggesting that these elements may play a crucial role in the occurrence of IUGR. In this review, we discuss the regulators of trophoblast syncytialization and their abnormal expression in the placentas of pregnancies complicated by IUGR.